BUSINESS LETTER AND ITS FEATURES IN ENGLISH AND UZBEK ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the features of business letters, highlighting their significance, structure, and best practices in both English and Uzbek contexts. Business letters are essential tools for professional communication, and understanding their elements is crucial for effective correspondence. The article examines the components of a business letter, providing guidelines for writing clear and professional letters that achieve their intended purpose.